Prevalence of Haemoplasma Infections in Stray Cats in Northern Italy. (23rd February 2014) - Spada, Eva; Proverbio, Daniela; Galluzzo, Paola; Della Pepa, Alessandra; Bagnagatti De Giorgi, Giada; Perego, Roberta; Ferro, Elisabetta
Abstract : This study investigated the prevalence of feline haemoplasma infections in a number of stray cat colonies in Milan, Northern Italy. Blood samples from 260 stray cats were evaluated, with conventional PCR, for the presence of DNA associated with Mycoplasma haemofelis (Mhf) and " Candidatus Mycoplasma haemominutum " (CMhm). Odd ratios (OR) were calculated to identify risk factors for haemoplasma infections. PCR was positive in 86 out of 260 subjects (33.1%), with a prevalence of 10.8% (28/260 cats) for Mhf and 22.3% (58/260 cats) for CMhm. No coinfections were registered. There were significant associations between infections and season of sampling, that is, a negative association between winter sampling and a haemoplasma positive status ( OR = 0.29, P = 0.001 ), or CMhm positive status ( OR = 0.29, P = 0.01 ) . Haemoplasma infections are common in stray cats in Milan. Thus, domestic cats with outdoor access should be routinely monitored and treated for ectoparasites to minimize risks of disease acquisition. Moreover, as these infections are transmitted via blood, feline blood donors from this area should be screened by PCR and preferably be drawn from a population of indoor cats regularly treated for fleas.